A decade of English academic reading research: A bibliometric analysis - Ismail, Hijril; Mukminin, Amirul; Lukman; Humaira; Edi (Edelweiss Applied Science and Technology, 2024)
This paper addresses a gap in the literature by conducting a bibliometric analysis of research on "English academic reading." The study aims to classify English academic reading articles, identify research trends, and explore popular and emerging topics in the field. To achieve these objectives, relevant articles were located using Publish or Perish software and assessed for quality using the Scimago Journal Rank (SJR). A total of 36 articles from 33 reputable journals, published between 2013 and 2023, were analyzed. Mendeley software managed references, while VOSviewer software classified the articles into six distinct research clusters. The most frequent keywords identified were ‘academic achievement,’ ‘academic reading,’ ‘students,’ ‘development,’ ‘English,’ and ‘case study.’ The analysis also revealed underexplored areas for future research, such as ‘academic performance,’ ‘English reading proficiency,’ and ‘extensive reading,’ among others. This study provides a comprehensive overview of the current research landscape on English academic reading. The findings highlight areas that have been extensively studied and suggest significant opportunities for further exploration. Researchers and educators can use these insights to develop more effective strategies to enhance English academic reading proficiency among students.